Ethical review of health research: a perspective from developing country researchers. Issue 1 (10th February 2004) - Hyder, A A; Wali, S A; Khan, A N; Teoh, N B; Kass, N E; Dawson, L
Abstract : Background: Increasing collaboration between industrialised and developing countries in human research studies has led to concerns regarding the potential exploitation of resource deprived countries. This study, commissioned by the former National Bioethics Advisory Commission of the United States, surveyed developing country researchers about their concerns and opinions regarding ethical review processes and the performance of developing country and US international review boards (IRBs). Methods: Contact lists from four international organisations were used to identify and survey 670 health researchers in developing countries. A questionnaire with 169 questions explored issues of IRB review, informed consent, and recommendations. Results: The majority of the developing country researchers were middle aged males who were physicians and were employed by educational institutions, carrying out research on part time basis. Forty four percent of the respondents reported that their studies were not reviewed by a developing country IRB or Ministry of Health and one third of these studies were funded by the US. During the review process issues such as the need for local language consent forms and letters for approval, and confidentiality protection of participants were raised by US IRBs in significantly higher proportions than by host country IRBs. Conclusion: This survey indicates the need for the ethical review of collaborative research in both US and host countries. It also reflects a desire for focused capacity development in supporting ethical review of research.